2018
DOI: 10.17576/jkmjc-2018-3402-08
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Political Socialization Agents on Pakistani Youth’s Political Participation: The Mediating Role of Media and Interpersonal Communication

Abstract: Apathetic and disconnected from the political world, these are just two of the titles scientists, journalists and politicians have been attributing to youth. Hence, what factors weaken or encourage youth to participate in politics is forefront in academic and non-academic researches. Hence, in view of this context, the role of political socialization agents in engendering political activities among youth cannot be overstated. However, not much research is being carried out in this area. Thus, this study assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(51 reference statements)
0
2
0
1
Order By: Relevance
“…The results showed that politically like-minded and dissimilar discussions play a significant mediating role between new media use and political participation. Similarly, Memon, Ishak, and Hamid (2018) argued that media influences political participation via interpersonal communication. The study of Xiaoming, Nainan, and George (2014) suggested the positive mediating role of political efficacy between online news and offline/online political participation.…”
Section: Political Participation (R2)mentioning
confidence: 99%
“…The results showed that politically like-minded and dissimilar discussions play a significant mediating role between new media use and political participation. Similarly, Memon, Ishak, and Hamid (2018) argued that media influences political participation via interpersonal communication. The study of Xiaoming, Nainan, and George (2014) suggested the positive mediating role of political efficacy between online news and offline/online political participation.…”
Section: Political Participation (R2)mentioning
confidence: 99%
“…Keluarga yang menggalakkan perkongsian idea dan emosi, meningkatkan tahap keterikatan golongan muda dengan keluarga (Memon, Ishak & Hamid, 2018). Fungsi keluarga dalam membantu golongan muda menyelesaikan masalah, membuat keputusan dan berkongsi emosi dijangka mengurangkan kecenderungan golongan muda mencari penyelesaian di luar rumah, di mana ini membuka ruang tindakan tidak berintegriti.…”
Section: Keterikatanunclassified
“…They have the capacity to exert a substantial impact on political stability. Youths who are empowered and politically literate can serve as catalysts for positive change, ensuring the responsiveness of democratic systems (Memon, 2018). Scholars and practitioners currently lack a thorough understanding of factors of peers' influence on youth political behavior.…”
Section: Introductionmentioning
confidence: 99%